Pengaruh Harga dan Kualitas Layanan Terhadap Keputusan Pembelian Konsumen Mie Gacoan di Cirebon - Putri, Rifda Labibah; Wulandari, Oryz Agnu Dian (Magister Manajemen Universitas Wisnuwardhana, 2024)
In the current era of digitalization, each company has a different product marketing strategy. One of them is by setting a product price strategy without reducing the quality of service that will influence consumer purchasing decisions. This study aims to determine the effect of price and service quality on consumer purchasing decisions for Mie Gacoan Cirebon. The type of method used in this research is quantitative method. Data collection techniques in this study using data from questionnaires distributed online. The population in this study were consumers of Mie Gacoan. The author used a nonprobability purposive sampling method which resulted in 100 respondents using the Smart PLS 4.0 analysis tool. The results in this study indicate that price and service quality have a positive and significant effect on consumer purchasing decisions for Mie Gacoan Cirebon.